The Knowledge, Attitude and Practice about cervical cancer among women of reproductive age living in Rawalpindi, Pakistan: A Cross-sectional study - Nazir, Fatima; Rasheed, Sara; Zaidi, Narjis; Chand, Komal; Iqbal, Laiba; Khola Noreen, Ayesha Masood, Mahnoor Qayum (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Abstract Background: Cervical cancer is a malignant epithelial tumor caused by Human papilloma virus. It is a gradually progressive disease. Since it is a prevalent health problem and can be prevented, it is necessary that women are aware of the disease and its prevention. This cross-sectional survey aimed to evaluate the knowledge, attitudes, and practices regarding cervical cancer among women of reproductive age group in Rawalpindi, Pakistan. Objectives: To assess knowledge, practice, and attitude of women of Rawalpindi regarding cervical cancer and to determine the association between knowledge, attitude and practices regarding cervical cancer and demographic factors Methods: A self-structured questionnaire was developed from a previous study (1). Random women of reproductive age (15-49) visiting Holy family Hospital, Rawalpindi were interviewed, and data was collected after informed consent in the time span of 3 months. Data was analyzed using SPSS (Statistical Package for Social Sciences) version 26. To find the association between independent variables (demographic characteristics) and dependent variables (Knowledge score, attitude score, practice score) an independent t test was used. Also, Pearson correlation was used to find association between knowledge score , attitude score and practice score . Results: Overall study showed that 152(66.6%) women had adequate level of knowledge, 119(52.1%) women showed adequate level of attitude towards cervical cancer and 204(89.4%) women showed adequate level of practice. Among these women majority of women were younger, unmarried, literate, and nulliparous. On using independent t test significant (p<0.05) association was found between marital status, parity, age, and knowledge score also, significant (p<0.05) association between parity and attitude score was found. And significant (p<0.05) association was found between age, marital status, parity, and practice score. Pearson correlation showed signification relation between knowledge score and attitude score , knowledge score and practice score . Conclusion: There is a dire need to increase awareness among women regarding cervical cancer to decrease the incidence of cervical cancer and to decrease mortality. Keywords: Cancer of Cervix , Cancer of the Uterine Cervix , Pap Smear , HPV